Recent Progress in Organometallic Chemistry - Muzibur Rahman, Mohammed; Mohamed Asiri, Abdullah (IntechOpen, 2017)
The book Recent Progress in Organometallic Chemistry mostly reviews the modem techniques and substantial organometallic and medical applications of inorganic materials. Chapters of this book are invited and contributed from the experts throughout the world from prominent researchers and scientists in the field of inorganic chemistry on organometallics and metallocenes. Each chapter provides technical and methodological details beyond the level found in typical journal articles or reviews and explores the application of organometallics, medicinal, inorganic, and catalysis to a significant problem in medical and catalysis, also providing a prospectus for the future. This book compiles with the expert knowledge of many specialists in the organic-inorganic synthesis and use of inorganic catalyst and metallocenes including chemical catalysis, biological catalysis, photo-electrocatalysis, bioassays, industrial catalysis, large-scale synthesis, micro-nanocatalyst, and so on in the field of fundamental and applied organometallic chemistry. Highlighting and importance are included on real and practical problems, ranging from industrial to medical applications and from single-multicells to animal to human objects. This offers the unique opportunity of exchanging and combining the scientist or researcher in organometallic chemistry in largely chemistry, biological, biomedical, physiological, metallocene, and inorganic chemistry fields.